Validation of models for traffic resulting from mobility in microcellular mobile broadband systems - Velez, Fernando J. (1998)
Approximate models for traffic resulting from mobility are presented and their validity is examined for a system without guard channels for handover. The blocking probability for both new and handover calls is assessed via a Markov chain, which can be approximated by a model that allows the use of the theory from Jackson networks. Some examples are given where the blocking and handover failure probabilities are computed; their approximation error being negligible in a wide range of coverage distances foreseen for mobile broadband system environments, mainly for the blocking probability. Although it is usual to consider the handover traffic as Poisson distributed, one can show that for homogeneous traffic in the whole coverage area this is not strictly necessary. The independence among the number of calls being served in each cell is also presented as a conclusion in the range of validity of the approximation.